Screening some pine species from North America and dried zones of western Asia for drought stress tolerance in terms of nutrients status, biochemical and physiological characteristics - Nouri, Karim; Nikbakht, Ali; Haghighi, Maryam; Etemadi, Nematollah; Rahimmalek, Mehdi; Szumny, Antoni (Frontiers in Plant Science, 2023)
Drought due to climate change or reduced precipitation is one of the main factors limiting the growth and establishment of plants and is one of the most critical challenges facing humans.To investigate the effect of different levels of drought stress on some pine species, this research was carried out as a factorial experiment using two factors and a completely randomized design. It included five populations of four pine species (Pinus brutia Ten. var. eldarica, P. nigra Arnold, P. mugo, and P. banksiana Lamb (including populations 8310055 and 8960049), and three levels of irrigation (100%, 75%, or 50% FC, denoted as normal, mild or intense drought stress, respectively) with three replicates. The findings showed that, photosynthetic pigments, relative water content, visual quality, the content of nutrients, protein content, and fresh and dry weight all decreased significantly when plants were exposed to intense drought stress. However, raised proline levels, electrolyte leakage percentage, soluble sugars levels, and antioxidant enzyme activity. We detected a decline in most growth traits 2 when comparing mild drought stress conditions to normal irrigation, yet acceptable quality seedlings when compared to intense drought stress. Intense drought stress had a substantial impact on many pine seedlings. PCA results showed that among different pine species, the level of resistance to drought is as follows: P. mugo> P. brutia var. eldarica> P. nigra> P. banksiana 8310055> P. banksiana 8960049. Our novel finding was that, P. mugo is a resistant species in arid and semi-arid regions, and P. banksiana species, especially its population of 8960049, is sensitive.